VERBAL COMMUNICATION ANALYSIS IN THE OPRAH WINFREY SHOW - Hani Nurfazrina (Indonesian EFL Journal, 2016)
This paper aims at finding verbal communication used by an interviewer and interviewee in Oprah Winfrey Show. The theory used in this research was Levines and Adelman theory. The data were taken from two different videos of Oprah Winfrey Show. This study used descriptive qualitative method. Based on the result of the research, in the first video, it was found 81 of high involvement and 129 of high considerateness used by Oprah and 54 of high involvement and 125 of high considerateness used by Thich, 21 directness and 20 indirectness used by Oprah and 18 directness and 21 indirectness used by Thich, 3 bowling conversational style applied by Oprah and Thich. In the second video, there were109 high involvement and 66 of high considerateness used by Oprah, 131 high involvement and 69 of high consideratness used by Alanis, 26 directness and 7 indirectness used by Oprah and 26 of directness and 7 of indirectness used by Alanis, and 1 ping-pong conversation used by Oprah and Alanis. In addition, there were the changes of communication style occured in the conversation between an interviewee and an interviewer in Oprah Winfrey Show that indicate that there are the influences of cultural background towards communication style.